Calidad de vida de las personas con discapacidad en relación con la funcionalidad familiar Loja 2016. - Verdugo Tinitana, Zairena Yosela (2017)
People with disabilities are a vulnerable group of our population wich requires priority attention and quality of life, since it is the human´s main aspiration of all time, is currently an indicator of well-being playing a role primary in the collection of evidence, especially to identify predictors of quality of life and the impact of targeting resources to maximize the positive effects; this research is justified since there is no study that relates this issue, whose general objective is to establish the relationship between the life quality of people with severe and very severe disability with family functionality in the province of Loja as well as to characterize the quality of life, family functionality, demographic and socio-economic factors in the stratum of the population; a not experimental, cross -correlational, study was performed in a sample of 397 people with severe and very severe disability, to whom a personal file, the Generalitat Cataluña (GENCAT) quality of life scale, the 2010 socio-economic conditions questionnaire of the Ecuadorian Institute of Statistics and Censuses; and the APGAR family functionality test were made. The data was examined from the univariate analysis and by means of the chi chart, using the SPSS v. 16 programs. The results show a prevalence of poor quality of life, moderate family dysfunction, and a statistically significant association between these variable. In conclusion, quality of life is directly related to familiar functionality, which will serve to generate strategies that will lead to improve for a better life. Key words: Disability, family functionality, risk factor, socioeconomic level.